Analisis Dampak Program Bantuan Pangan Non-Tunai terhadap Pengeluaran Konsumsi Rumah Tangga Pertanian di Maluku - Ridha, M. Rismawan; Rumayya, Rumayya (UI Scholars Hub, 2024)
Poor households in the agricultural sector belong to a group with high food insecurity. As one of the instruments in overcoming the problem of food insecurity, Non-Cash Food Assistance (BPNT) provides social assistance to the poor to purchase adequate and nutritious food. This study aims to analyze the impact of BPNT on the expenditure of poor households in the agricultural sector in Maluku province. Using the Propensity Score Matching analysis on March 2020 Susenas data, the results show that BPNT significantly influences increasing food expenditure but not total expenditure.